How to Increase Savonius Power Coefficient: Ducted Rotor Performance with Different Overlap Ratios. Issue 1 (1st December 2022) - Brusca, S; Galvagno, A; Lanzafame, R; Mauro, S; Messina, M
Abstract: The use of ducted configuration to increase the efficiency of wind turbine rotors is gaining wide attention in the scientific community. Specifically for mini and micro rotors in urban environment applications this solution demonstrated to be very attractive. The possibility to overcome the Betz limit for power coefficient was widely demonstrated in ducted horizontal axis wind turbines. However, very few studies have dealt with ducted Savonius rotor despite these rotors represented an efficient solution for urban environment thanks to their simplicity, their cheapness and the low cut in velocity in highly turbulent conditions as well. Furthermore, the ducted Savonius concept, might be applicable to oscillating water column wave energy devices, thanks to its self-rectifying capability and simplicity. For these reasons, the authors carried out an experimental campaign to verify the impact of ducting the Savonius rotor, thus leading the way for a possible exploitation of this configuration in many practical applications. Specifically, The present paper deals with a study of ducted Savonius type air turbine performance. In particular, turbine performance was studied as a function of turbine overlap ratio. Four overlap ratios were tested: 0, 1/6, 1/3 and 1/2. A specific experimental setup was built to test ducted turbine, while bare turbine performance was measured using a wind tunnel. All tests were performed at fixed air velocity: 5 m/s. On the basis of the results, it is possible to state that ducted turbine performance is higher than bare turbine performance, at all tip speed ratios and for all overlap ratios. The optimal turbine overlap ratio is equal of 1/3.